The Effectiveness of Augmented Reality as a Learning Tool in Enhancing Elementary School Students’ Motivation in Science and Social Studies - Raihan Nur Akmal; Suharman; Maya Agustina; Gamal Barqie; Wan Marfazila Binti Wan Mahmud (Universitas Syiah Kuala, 2026)
Low student learning motivation in ilmu pengetahuan alam dan sosial (IPAS) at the elementary school level remains a major issue due to the use of less interactive learning media. This condition leads to low student engagement in the learning process. Therefore, this study aims to examine the effectiveness of augmented reality (AR) media in enhancing students’ learning motivation in IPAS among fourth-grade students at MIN 8 Aceh Barat. This study employed a quantitative approach with a quasi-experimental design. The research population consisted of all students at MIN 8 Aceh Barat, with class IV B as the experimental group and class IV C as the control group. The instrument used was a learning motivation questionnaire administered before and after the treatment. Data were analyzed using an independent samples t-test to compare learning motivation between the two groups. The results showed that before the treatment, there was no significant difference between the two groups (p = 0.481 > 0.05). After the implementation of AR, students’ learning motivation in the experimental group was significantly higher than that in the control group (p = 0.0005 < 0.05). These findings were supported by observations and interviews, which indicated increased student participation, interest, and enthusiasm. Therefore, the use of augmented reality media is proven to be effective in improving students’ learning motivation in IPAS